Public Communication Strategy Management at the Sumedang DPRD in Publishing Information - Febianti, Fepi; Sudrajat, Arip Rahman (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2019)
Strategy management is  the art and science of formulating, implementing, and evaluating cross-functional decisions that enable organizations to achieve goals.Each local government certainly has a vision and goals in regional management, including matters related to regional development. Regional development policies are based on the characteristics of the region itself. Including what happened in the Sumedang Regency area. Public relations is a part of the company that acts as a liaison between the company and the community and establishes good relations with the community. Every activity carried out by the DPRD of Sumedang Regency, West Java Province, is always in the public spotlight, therefore publications are needed so that the public knows all matters related to Board Members. Through news that has been published in the mass media, opinions will form among the public. The purpose of this study is to find out how the public communication strategy in the Sumedang Regency DPRD is designed to ensure effectiveness in publishing information, knowing concrete steps taken to increase transparency and openness in conveying information to the community, how the Sumedang Regency DPRD plans to involve the community in the process of delivering information and decision making. The object of this study and research is public relations activities in publishing information through mass media to the public. The methods used in data collection are observation, interviews, and documentation. Data were collected and analyzed using descriptive qualitative methods. The results of this study, namely public relations and other DPRD members are closely related in establishing harmonious relationships with the public in publishing information to the public in order to create transparency in all matters.